Fort Collins Flood 1997: lessons from an extreme event - Grigg, Neil S., author; Doesken, Nolan J., author; Frick, David M., author; Grimm, Mike, author; Hilmes, Marshi, author; McKee, Thomas B., author; Oltjenbruns, Kevin A., author (Colorado State University. Libraries, 1998)
The July 28, 1997 flood disaster in Fort Collins, Colorado is generally called a "500-year event" and offers insight into the causes and impacts of extreme urban flooding. Although it hurt and traumatized many people, the flood provided valuable lessons for civil engineers, managers of government agencies, political leaders, counselors, and citizens. Representing several disciplines and entities, the authors present a cross-cutting view of the flood emergency and its lessons. The paper also includes a synthesis of a post-flood conference at Colorado State University which featured reports from all major entities involved in the flood. The remarkable storm that caused the flood produced the heaviest rains ever documented to have fallen over an urbanized area in this state in the recorded history of Colorado. The storm occurred in stages, and dropped 10 to 14 inches in 31 hours in a large area around Fort Collins. The heaviest hourly precipitation occurred at the storm's end, which is different from most storms, and may have exacerbated the flooding. Runoff was dramatic and some peak discharges greatly exceeded projected 100-year and 500-year flows. The City Manager's report showed five people dead, 54 people injured, loss of about 200 homes, and 1500 homes and businesses damaged throughout the City. Fort Collins was more prepared than most cities because it has a nationally-recognized Stormwater Utility and good emergency response capabilities, but it still learned much from the event. Damages at Colorado State University were unusually severe, totaling in the range of $100 million, including building damages, about 425,000 library volumes inundated, loss of a semester's textbooks in the bookstore, and many other losses-both personal and professional. Although the university was surprisingly vulnerable, it responded well with no delay in opening school a month later, but only as a result of tremendous efforts. Emergency response in the City by the Poudre Fire Authority was outstanding, and although the flood had tremendous impacts on the community, not one firefighter or police officer was injured. Within three months after the flood, the local paper, the Coloradoan, had published 282 stories about the flood, and the event received broad coverage in the United States and abroad. After the flood, Fort Collins has tried to focus beyond the physical issues to recognize the multi-faceted losses and the ensuing grief experienced by many people. Lessons are presented in the paper about complacency, protecting vulnerable areas, flood frequency analysis, stress and trauma, the importance of organizational mobilization, the vulnerability of universities, growth management in a hazardous environment, mitigation versus response, communicating risk to officials and the public, and handling large influxes of donations.
Keywords: Floods -- Colorado -- Fort Collins; Flood damage -- Colorado -- Fort Collins; Flood control -- Colorado -- Fort Collins